PHYSICAL PROTECTOR IN DIRECT SOWING OF BARU INFLUENCING IN THE INITIAL GROWTH OF THE SEEDLINGS (REVISTA DE AGRICULTURA NEOTROPICAL, 2018)
The objective of this study was to evaluate the influence of using physical protectors on the emergence and initial growth of Baru seedlings in a direct sowing system. The experiment was installed in a randomized complete block design, testing the use of physical protectors (no protection, P0; plastic cup (500 mL) without the bottom, P1; laminated wood, P2), with 12 repetitions. Weekly soil temperature monitoring was carried out in the morning and in the afternoon in the period between 14 and 56 days after sowing (DAS). Daily emergence follow-up was also performed, and the stem diameter, total height and number of leaves were measured at 81 DAS. The use of physical protectors in the direct seeding of Baru interfered in the soil surface temperature on the sowing point, on the seedling emergence speed index, seedling survival, stem diameter and seedling height. Implementing protectors slowed the seedling emergence speed, however it provided higher percentages of emergence, survival and greater growth in diameter and height.